2016
DOI: 10.1063/1.4948466
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemical structure on the magnetic and electronic properties of Co2FeAl0.5Si0.5/Si(111) interface

Abstract: We show that Co2FeAl0.5Si0.5 film deposited on Si(111) has a single crystal structure and twin related epitaxial relationship with the substrate. Sub-nanometer electron energy loss spectroscopy shows that in a narrow interface region there is a mutual inter-diffusion dominated by Si and Co. Atomic resolution aberration-corrected scanning transmission electron microscopy reveals that the film has B2 ordering. The film lattice structure is unaltered even at the interface due to the substitutional nature of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
(33 reference statements)
4
22
0
Order By: Relevance
“…1c calculated assuming the twinned epitaxial relationship shows excellent correspondence with the experimental diffraction pattern. A similar twinning phenomenon at interfaces has been also observed when a CFAS film is grown on Si(111)2.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…1c calculated assuming the twinned epitaxial relationship shows excellent correspondence with the experimental diffraction pattern. A similar twinning phenomenon at interfaces has been also observed when a CFAS film is grown on Si(111)2.…”
Section: Resultssupporting
confidence: 69%
“…Significant research activities have been devoted to create half-metal/semiconductor interfaces. Recent work has shown that CFAS/Si interface suffers from a number of challenges to meet the requirements for a chemically and structurally abrupt ferromagnet/semiconductor interface2. Due to the strong out-diffusion of Si (even at room temperature) as well as the sizable lattice mismatch of ~4.5% between CFAS and Si, non-magnetic thermodynamically stable phases (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence it is the aim of continuous experimental and theoretical research to control chemical intermixing arising due to interdiffusion, as well as interface strain, which are the main parameters that control the structural and chemical quality of a given heterostructure. However, tailoring the atomic structure of ferromagnet/semiconductor interfaces, of crucial importance for spintronic applications, has been shown to be a rather elusive goal despite the intensive research efforts over the past years [1,2].In this work, in the case of half metallic Co 2 FeAl 0.5 Si 0.5 (CFAS) and Ge we demonstrate that atomically sharp half metal/semiconductor interfaces are achievable with almost no strain due to the excellent lattice match between CFAS and Ge. We show that the film has the desirable B2 ordering which provides high spin polarisation and it does not form any secondary phases in the interface region.…”
mentioning
confidence: 99%
“…Hence it is the aim of continuous experimental and theoretical research to control chemical intermixing arising due to interdiffusion, as well as interface strain, which are the main parameters that control the structural and chemical quality of a given heterostructure. However, tailoring the atomic structure of ferromagnet/semiconductor interfaces, of crucial importance for spintronic applications, has been shown to be a rather elusive goal despite the intensive research efforts over the past years [1,2].…”
mentioning
confidence: 99%